MODEL OPTIMASI LINIER DETERIORATION OF DETERMINISTIC DEMAND DENGAN STRATEGI PEMASARAN DUA VERSI PRODUK - Wahyu Condro Kurniawan MS (Jurnal Matematika, 2016)
ABSTRACT. There is a condition where is the price of a product is not appropriate with consumen desirability because the quality of product is incompatible or market segment is not quite fit with the quality of the product due to competition with another trademark that will impact on demand. In this undergraduated thesis investigate about Linier Deterioration of Deterministic Demand optimization model  with two versions of the product marketing strategy which is a model to solve determination price problem and optimal quantity of deluxe products and regular products. An example of problem taken from one food product satu green beans “Bu Ati” use to describe the mechanism of model in determining the optimal policy and appropriate.